Identification and chromosomal distribution of copia-like retrotransposon sequences in the coffee (coffea l.) genome (2013)
The presence of copia-like transposable elements in seven coffee (Coffea sp.) species, including the cultivated Coffea arabica, was investigated. The highly conserved domains of the reverse transcriptase (RT) present in the copia retrotransposons were amplified by PCR using degenerated primers. Fragments of roughly 300 bp were obtained and the nucleotide sequence was determined for 36 clones, 19 of which showed good quality.The deduced amino acid sequences were compared by multiple alignment analysis. The data suggested two distinct coffee RT groups, designated as CRTG1 and CRTG2. The sequence identities among the groups ranged from 52 to 60% for CRTG1 and 74 to 85% for CRTG2. The multiple alignment analysis revealed that some of the clones in CRTG1 were closely related to the representative elements present in other plant species such asBrassica napus, Populus ciliata and Picea abis. Furthermore,the chromosomal localization of the RT domains in C. arabicaand their putative ancestors was investigated by fluorescence in situ hybridization (FISH) analysis. FISH signals were observed throughout the chromosomes following a similar dispersed pattern with some localized regions exhibiting higher concentrationsof those elements, providing new evidence of their relativeconservation and stability in the coffee genome.